The Reception of René Girard in Mexico. - Muñoz, Jorge Federico Márquez (Contagion: Journal of Violence, Mimesis & Culture, 2025)
The article focuses on the limited and fragmented reception of René Girard's thought in Mexico, shaped by foreign influences and informal academic efforts. Topics include the initial indirect references through Ivan Illich's intellectual circle, the gradual introduction of Girard's ideas in Mexican universities during the 1990s and 2000s, and the recent emergence of a small but growing network of scholars engaging with Girardian theory.